Hemodialysis employing molecular hydrogen (H2) enriched dialysis solution may improve dialysis related fatigue through impact on energy metabolism - Masaaki Nakayama; Kimio Watanabe; Emiko Sato; Yugo Ito; Nozomi Kadota; Kasumi Konishi; Chiharu Aizawa; Yukio Maruyama; Takuya Fujimaru; Masahiko Nagahama; Fumika Taki; Michiko Suzuki (Scientific Reports, 2025)
Abstract Hemodialysis employing molecular hydrogen (H2)-enriched dialysis solution rendered by water electrolysis (E-HD), has been reported to alleviate dialysis-related fatigue, but its association with metabolic profiles remains unclear. Eighty-one patients undergoing standard HD were classified into 3 groups [Group A (n = 25, 30.9%): fatigue with activity reduction—subgroups A1: chronic persistent fatigue (n = 11), A2: fatigue only on dialysis days (n = 14); Group B: fatigue without activity reduction (n = 24, 29.6%); Group C (n = 32, 39.5%): no fatigue], and their changes in fatigue, body composition, and metabolic profiles were studied following 12 months of E-HD. There were no significant differences in baseline characteristics among the groups. Over the 12 months after E-HD initiation, fatigue in Group A significantly decreased, while no changes in Group-B and C. Bio-impedance analysis revealed no significant changes in A1, but significant reductions in body fat and increases in skeletal muscle mass were observed despite no significant weight change in A2. Enrichment analysis suggested significant differences in metabolic pathways such as fatty acid metabolism, citric acid cycle, and glycolysis between Groups A and C at baseline, and these differences were mitigated by E-HD. E-HD could suppress dialysis-related fatigue, through possible involvement of altered energy metabolism of patients. E-HD may represent a new paradigm for uremia treatment beyond traditional solute removal-based dialysis therapies.